Сравнительная оценка энергозатрат ректификации частично растворимых компонентов смеси фурфурол-вода при различных способах орошения и питания колонны - Гарев, Андрей Олегович; Чернышев, И. С.; Бабак, Татьяна Геннадиевна; Балаба, Ю. О.; Колесник, Е. А.; Сильченко, К. А. (НТУ "ХПИ", 2010)
The comparative estimation of power consumption of rectification process was given for various kinds of feeding and refluxing of a column. The problem of optimal energy recovery for various types of the process organization was solved by pinch-analysis methods.
Keywords: азеотропные системы; растворимость; энергосбережение; ректификация; фурфурол; энергозатраты